Enabling policies for circular economy and climate change mitigation in rice production in Southeast Asia - Mirzabaev, Alisher; Antonio, Ronald Jeremy; Connor, Melanie; Nelson, Katherine; Saito, Kazuki; Sander, Bjoern Ole (International Rice Research Institute, 2024)
This report delves into the urgent challenge of adapting to climate change impacts on Southeast Asia’s globally vital rice production systems through addressing the sector’s significant contribution to greenhouse gas emissions. It explores innovative no-regret solutions and enabling policies to foster low-emission, climate-resilient, and circular economy-oriented rice systems, focusing on technological solutions, regulatory frameworks, and market mechanisms. By integrating strategies such as adoption of methane-reducing rice production practices, rice straw valorization, and circular economy development, the report outlines actionable pathways to enhance farmer resilience, promote sustainability, and secure the region’s role in global food security amidst growing environmental challenges.